(untitled) (Journal of Economic Research & Business Administration, 2019)
The theme of capital structure has always causes a lot of discussions between researchers. Managers should take into account various and contradictory factors presented in the studies when they make financial decisions. It is difficult to achieve an optimal capital structure taking into the specifics of companies in the small business segment. There is no model of optimal capital structure that can be accessed by all equally. Therefore, it is important to know the factors affecting the capital structure. The aim of this paper is to test how firm characteristics affect agricultural small busines’ capital structure in Kazakhstan. It discusses the effect of selected determinants on the capital structure of businesses, expressed by way of three categories of indebtedness. The analysis of the determinants of capital structure is conducted by way of panel regression. The panel data for the article were acquired from the Agency of statistics database. Specifically, the data used were those from accounting statements for the years 2015 – 2017 for the agricultural businesses of legal entities. In total, the object of examination was 50 small businesses. The results show that financial decisions correspond to the Pecking-order theory and in some cases to the Agency theory. Most of the factors considered in empirical studies are not significant. It is established that for all periods of debt, the impact of profitability on the small businesses capital structure is statistically significant, as well as the impact of the asset tangibility and the firm size in short-term debt.